ANALISIS KEANDALAN PROTOCOL VIRTUAL LOCAL AREA NETWORK (VLAN) UNTUK MENUNJANG KEAMANAN TRANSAKSI DATA ANTAR JARINGAN - Retriani Banobe; Petrus Katemba (Jurnal Publikasi Manajemen Informatika, 2026)
RETRIANI BANOBE Implementation of a Virtual Local Area Network (VLAN) to support data transactions between networks. Supervised by PETERUS KATEMBA Virtual Local Area Network (VLAN) is a network technology that can physically separate a network into several smaller network segments. This means that devices in one Virtual Local Area Network (VLAN) can only communicate with other devices in the same Virtual Local Area Network (VLAN) via a router. Virtual Local Area Network (VLAN) aims to reduce the amount of broadcast traffic for each subnet. Mikrotik is used to create a new Virtual Local Area Network (VLAN) and configure different inter-VLAN routing to communicate with each other. A switch is a network device that works at the data link layer of the OSI model. Each VLAN will have its own broadcast domain so that broadcast traffic will only be sent to the same Virtual Local Area Network (VLAN) device. Switches add Virtual Local Area Network (VLAN) tags to data frames passing through ports configured as trunk ports. Winbox provides a user-friendly interface for creating and managing Virtual Local Area Networks (VLANs) on a proxy and assigns IP addresses automatically to devices in VLAN by configuring the DHCP server on the proxy. The proposed network topology includes connected network devices with a trunking configuration to prevent data collisions, as well as assigning IP statistical addresses to each computer, aiming to improve network performance with a bandwidth of 100 Mbps.